Fuzzy Control Based Inventory System in food and beverage stores - Bambang Nurdewanto (Jurnal Penelitian, 2005)
To determine the optimal amount of food and beverage inventory, a control system is needed based on the level of sales and expiration. There are so many control systems today that want output that has high accuracy, so the control system requires a fairly complex system. With the fuzzy system, there is no need for a very complex control system.